2020
DOI: 10.5334/aogh.2889
|View full text |Cite
|
Sign up to set email alerts
|

Female Sex Workers’ Experiences of Violence and Substance Use on the Haitian, Dominican Republic Border

Abstract: Background: Female sex workers (FSW) are socially and economically marginalized, and this vulnerability can be exacerbated when they hold the intersectional identity of also being an immigrant, such as in the case of Haitian FSWs in the Dominican Republic. Objective: Considering that half of migratory young women and girls relocating across the Latin American and Caribbean region do so without their families, increasing the likelihood of experiencing abuses, our primary objective was to test the hypothesis tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Risk for IPV and for negative consequences related to IPV is also heightened for lower income women in rural communities, meaning that women of Haitian descent living in the DR, who face economic disadvantage and who often must live in more rural communities with fewer barriers, are additionally at higher risk of IPV (Gustafsson et al, 2016). Risk may also be elevated for women of Haitian descent living in the DR compared to women living in Haiti, as Hearld et al (2020) found when comparing victimization among female sex workers of Haitian descent in both countries.…”
Section: Women Of Haitian Descent In the Drmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk for IPV and for negative consequences related to IPV is also heightened for lower income women in rural communities, meaning that women of Haitian descent living in the DR, who face economic disadvantage and who often must live in more rural communities with fewer barriers, are additionally at higher risk of IPV (Gustafsson et al, 2016). Risk may also be elevated for women of Haitian descent living in the DR compared to women living in Haiti, as Hearld et al (2020) found when comparing victimization among female sex workers of Haitian descent in both countries.…”
Section: Women Of Haitian Descent In the Drmentioning
confidence: 99%
“…Comparatively, research on women’s experiences of IPV and violence tend to focus on Western populations, which, though valuable for those contexts, neglects the realities of women in the Global South (Renzetti & Edleson, 2008). The little research examining violence experienced among women of Haitian descent living in the DR has primarily focused on Haitian nationals immigrating to or working within the DR (Hearld et al, 2020; Petrozziello & Wooding, 2013). While important, this work does capture potentially unique experiences of women of Haitian descent born in the DR, but who were denied documentation due to xenophobic laws.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Promoting HIV knowledge-including the understanding of modes of transmission and prevention methods-to key populations, including commercial, cisgender female, and transgender female sex workers is at the foundation of HIV-related public health interventions and risk-reduction strategies (1)(2)(3). The Latin America and Caribbean (LAC) region has high rates of HIV, second only to Sub-Saharan Africa; female sex workers in the LAC region are at exacerbated risk for HIV due to their low socioeconomic status, stigmatized and powerless role in society, and residence in nations that criminalize sex work making it difficult if not impossible for victimized sex workers to seek protections though police and legal channels (4)(5)(6). Haiti is a low income country and, within the LAC region, holds the highest national rate of poverty, leading to some of its most vulnerable residents being forced into sex work to support their families (2,7).…”
Section: Introductionmentioning
confidence: 99%